An ethnobotanical survey on the therapeutic use of Cannabis sativa L. in the province of Taounate, Morocco. - Balafrej, Taha; Skalli, Souad; Benaich, Souad; Bessi, Aymane; El Mekkaoui, Anas; Boukour, Basma; Mehdad, Slimane; Zaid, Younes; Rais, Saadia; Rais, Chaimae; Benlakhdar, Said; Hassikou, Rachida (Ethnobotany Research and Applications, 2024)
Background: Cannabis has been used for over 4,500 years in different area, including medicine, to treat many illnesses. This study was to investigate to carry out an ethnobotanical survey to collect information on therapeutic uses of this plant by local population. Methods: Ethnobotanical study was conducted in Taounate province using semi-structured interviews with random informants. The data was analysed using statistical indices and tests as cultural Importance (CI), fidelity level (FL), relative frequency of citation (RFC), Chi square () test, logistic regression, multiple corresponding analysis (MCA), and Non-metric multi-dimensional scaling (nMDS). Results: 65.4 % of the informants used Cannabis sativa L. Among them, therapeutic use showed a CI of 0.40. 11 diseases were found to be treated by cannabis. The most recommended preparation method was smoking, and the most common administration method was inhalation. Cham was the most cited ailment with a FL of 92.9 %. Results showed a significant correlation of therapeutic use with sex and type of locality. MCA revealed that people using cannabis for therapeutic use were sharing common trait with male, urban areas, secondary education level, and informants aged between 20 to 40 years. Then, Nmds showed that the treated disease were uniformly dispersed between rural and urban locality. Conclusion: The present study highlights the importance of therapeutic use of Cannabis sativa L. in Taounate province. However, more in-depth phytochemical, pharmacological, toxicological, and clinical research is needed to investigate its effectiveness and safety. Keywords: Cannabis sativa L., survey, ethnobotany, Taounate, therapeutic use.